STEAM Education Concept in English Teaching Practice Process Based on Big Data Evolutionary Network Influence Analysis - Guo, Minmin (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: English language teaching in China is primarily traditional test-based education. Few teachers customize teaching activities according to the content and students' characteristics, which results in students' low interest in learning English and reduces their understanding and application of knowledge to the point that their speaking skills are generally weak. English is different from Chinese in that it combines skills and practice and covers a wide range of knowledge. It is a subject category that combines general knowledge of life with theoretical knowledge. Although it is only a language subject, in the process of learning it, students can also learn the human background, customs, history and culture of foreign countries, enriching their understanding of world culture.OBJECTIVES: Organic combination of the STEAM model and English teaching can promote academic innovation, on the one hand, to enhance learning hobbies from the aspect of learning needs and to cultivate students' comprehensive literacy, and on the other hand, the innovation of practice and concepts can enhance students' practical ability and innovation ability.METHODS: This study is based on big data evolutionary network influence analysis of STEAM education concept in English teaching time process analysis of students in the classroom participation, interest in learning English and learning self-confidence and the phenomenon of mismatch between the students' learning foundation, to enhance the student's classroom participation, the interest in learning English and self-confidence, the students' comprehensive literacy, and the acquisition of English language skills.RESULTS: STEAM + ELT practices + interdisciplinary teaching can be realized by organically combining STEAM education concepts across multiple subject areas.CONCLUSION: Designing appropriate English teaching activities based on the STEAM education concept and applying the theory in actual teaching activities can achieve the expected results.
Keywords: STEAM education concept; English teaching; big data